Comparative Study of Mediation Practices in Financial Disputes Between Indonesia’s LAPS SJK and Singapore’s FIDReC Framework - Handriyanto Wijaya; Dewi Sulistianingsih; Irawaty (Kosmik Hukum, 2026)
This article conducts a doctrinal and comparative analysis of Indonesia’s LAPS-SJK and Singapore’s FIDReC to examine how institutional design shapes fairness, accessibility, and legitimacy in financial dispute resolution. Drawing on normative legal methods and qualitative thematic analysis, the study evaluates each institution’s governance structure, mediation model, procedural architecture, transparency practices, and enforcement mechanisms. The comparison shows that the two bodies are grounded in distinct regulatory logics that produce markedly different capacities to mitigate information asymmetry in financial disputes. LAPS-SJK adopts a facilitative mediation model that emphasises party autonomy and mediator neutrality. In practice, however, this approach proves inadequate in an environment where consumers face complex financial products and substantial informational disadvantages. The absence of evaluative guidance, combined with a single-tier dispute-resolution structure, limited transparency, and weak enforcement, often restricts consumers’ ability to secure substantively fair outcomes. These features risk reinforcing rather than correcting existing power imbalances. FIDReC, by contrast, employs a hybrid mediation model that permits evaluative input and is supported by a two-tier system in which adjudication operates as a safeguard against unfair settlements. Its robust transparency regime—featuring detailed annual reports and anonymised case summaries—enhances institutional accountability and predictability. Binding outcomes backed by MAS oversight further strengthen compliance and user confidence. The study concludes that effective financial dispute resolution requires more than statutory mandates; it depends on institutional capacity, regulatory coherence, and mechanisms that actively address structural inequalities. The contrasting experiences of LAPS-SJK and FIDReC highlight the importance of transparency, evaluative support, and enforceability in promoting procedural justice and institutional legitimacy.